The allocation of liability in Latvian law for construction delicts: the reach for the compensation - Daukša, Diāna (Riga Graduate School of Law, 2018)
The theme of the thesis is the allocation of civil liability for damage caused to third parties by a structure fully or partly collapsing during the exploitation period due to errors made during the construction period and, therefore, the injured party’s possibility of receiving compensation from the liable construction participant. The aim of the work is to analyse and assess the existing legal framework and its application in practice in order to identify the main issues within the existing compensation mechanism and to determine necessary modifications, in order for there to exist an appropriate, internally coordinated, fair, effective and proportionate legal mechanism.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Contract law; Construction contracts; Civil liability